Book Review: Islamicity Indices, The Seed for Change - Riani, Ririn (SMART Insight, 2025)
The book Islamicity Indices: The Seed for Change by Hossein Askari and Hossein Mohammadkhan (2016) introduces a quantitative framework to measure the extent to which countries apply Islamic values in their social, economic, and political practices. Through five main indices—economic, legal and governance, human and political rights, international relations, and an overall index—the authors reveal that many non-Muslim countries are precisely more